The Perception of Customer Value and its Influence to Self Consept in using Credit Card - Wijayanto, Gatot; Suryana, Yuyus; Oesman, Yevis Marty; Helmi, Arief (International Review of Management and Marketing, 2019)
Credit cards are one way to facilitate buying and selling transactions involving banks / issuing companies, credit card holders and sellers. Banking is quite optimistic in the future, the credit card business can provide significant benefits. In the practice of using credit cards, there are often a number of problems experienced by customers in the form of complaints on the use of credit cards that range from late delivery of bills that have an impact on charging bills, card transactions not read by EDC machines, and also lack of information provided by officers credit card when offering to prospective customers. Reviewing these problems, the purpose of this study examines the impact of customer value on the self-concept of using a credit card The research method used is descriptive verification with an approach using structural analysis equation modeling method which is carried out by distributing questionnaires to 400 credit card user customers in the 3 largest credit card issuing banks in Indonesia in 2016 and credit cards still actively used by their customers, namely banks independent, BCA bank, and BNI bank. Based on the results of data analysis and problem facts, it was found that the self concept variable was able to influence the relationship between the effect of customer value on the decision to use. Innovation from the findings of this research model is that self-concept is customer behavior that can be considered by banks / publishing companies that can determine the decision making of credit card use. Keywords: Customer Value, Self Concept and Use Decision, Credit Card JEL Classifications: D1, G2 DOI: https://doi.org/10.32479/irmm.7817